Strigolactone treatment enhances resistance to black spot in korla fragrant pear by activating Ca2 + /NO signaling and maintaining reactive oxygen species homeostasis - Xin Zhang; Wenhui Cheng; Xianmei Xiao; Shaocong Ma; Yuanyuan Hou; Yating Zhao (Postharvest Biology and Technology, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Correction to: Automated machine learning-based reverse osmosis membrane flux prediction and chemical dosage dynamic adjustment - Zhiyang Cheng; Yang Yu; Xia Meng; Yating Wang; Fangong Kong; Minghua Zhou; Jie Wang (ENGINEERING Environment, 2026)

Constructing of an NH2-MIL-53(Fe)/g-C3N4 adsorptive photo-Fenton system for efficient degradation of norfloxacin in medical wastewater - Ziqi Deng; Yating Chen; Pengjun Duan; Rong Cheng; Jianzhong Zheng; Xiang Zheng (Chemical Engineering Journal, 2026)

Automated machine learning-based reverse osmosis membrane flux prediction and chemical dosage dynamic adjustment - Zhiyang Cheng; Yang Yu; Xia Meng; Yating Wang; Fangong Kong; Minghua Zhou; Jie Wang (ENGINEERING Environment, 2026)

Perfluoroalkyl substance pollutants disrupt microglia function and trigger transcriptional and epigenomic changes - Yating Cheng; Jian-Rong Li; Hangjin Yu; Shuang Li; Boranai Tychhon; Chao Cheng; Yi-Lan Weng (Toxicology, 2025)

Integration of transcriptomics and metabolomics reveals the role of methyl jasmonate in alleviating chilling injury of postharvest prune fruit - Yating Zhao; Yuanyuan Hou; Xianmei Xiao; Yingjie Wu; Xin Zhang; Baoxiang Li; Wenhui Cheng; Xuan Zhu; Jianye Chen (Postharvest Biology and Technology, 2025)

Community Distribution of Endophytic Bacteria in Nodules of Vicia villosa in Rocky Desertification Area of Southwest China - Yuanyuan Qi; Jinhuan Cheng; Xinyue Zhang; Li Yao; Yating He; Qiuli Yan; Jinhua Wang (Current Microbiology, 2025)

Gastrodin promotes ferroptosis in CRC cells by inhibiting SKP2 to reduce NCOA4 ubiquitination - Qiao Zhang; Zhijie Xu; Wanying Liu; Zhidong Cheng; Yating Ding; Yafeng Xie; Shengyu Yan (Tissue and Cell, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

Anchoring nanoscale zero-valent iron within bacterial cellulose particles for boosting efficient adsorption of Co(II) and Sr(II) from seawater: Dual system and varying adsorption mechanisms - Rong Cheng; Yating Chen; Mi Kang; Peiwen Jiang; Lei Shi; Jianzhong Zheng; Xiang Zheng; Jianlong Wang (Journal of Environmental Sciences, 2025)

Identification and validation of oxidative stress-related diagnostic markers for recurrent pregnancy loss: insights from machine learning and molecular analysis - Hui Hu; Li Yu; Yating Cheng; Yao Xiong; Daoxi Qi; Boyu Li; Xiaokang Zhang; Fang Zheng (Molecular Diversity, 2025)

GhCTEF2 encodes a PLS-type PPR protein required for chloroplast development and plastid RNA editing in cotton - Huan He; Mengxue Cheng; Bowen Bao; Yanan Tian; Yating Zheng; Yuzhu Huo; Zengqiang Zhao; Zongming Xie; Jianing Yu; Peng He (Plant Science, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Evaluating the influence of alternating flooding and drainage on antimony speciation and translocation in a soil-rice system - Zhao Chen; Bingqing Xia; Yang Yang; Shiwen Hu; Kuan Cheng; Pengfei Cheng; Shan Wang; Guojun Chen; Qi Wang; Haibo Dong; Chao Guo; Yating Chen; et al. (Science of The Total Environment, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Design and assessment of highly stable norfloxacin/ Ca-montmorillonite (STx-1b) as oral beads - Po-Hsiang Chang; Chenxing Liang; Yating Yang; Yaqi Wen; Cheng-I Lee; Juin-Yen Ho; Chien-Yen Chen; Yu-Min Tzou (Applied Clay Science, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Autophagy inhibition mediated by trillin promotes apoptosis in hepatocellular carcinoma cells via activation of mTOR/STAT3 signaling - Guangjie Zhan; Tiantian Wei; Huichen Xie; Xiaoming Xie; Jun Hu; Hao Tang; Yating Cheng; Huaifeng Liu; Shujing Li; Guohua Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Analyzing the impact of natural capital on socio- economic objectives under the framework of sustainable development goals - Yating Dai; Yuze Ding; Shuya Fu; Lixin Zhang; Jian Cheng; Daolin Zhu (Environmental Impact Assessment Review, 2024)

Optimizing the binding of OGT and a peptidic substrate towards pseudo-substrate inhibitors via molecular dynamic simulations - Xinfang Qin; Jie Shi; Xia Li; Mingming Lu; Yating Zhu; Qiyuan Yang; Zhimeng Wu; Cheng Lu (Systems Microbiology and Biomanufacturing, 2024)

Sodium butyrate alleviates deoxynivalenol-induced porcine intestinal barrier disruption by promoting mitochondrial homeostasis via PCK2 signaling - Dongfang Xue; Yating Cheng; Tiantian Pang; Yunyi Kuai; Yu An; Kuntan Wu; Yuqing Li; Mengyu Lai; Bihan Wang; Shuai Wang (Journal of Hazardous Materials, 2023)

Deeply removal of trace Cd2+ from water by bacterial cellulose membrane loaded with nanoscale zerovalent iron: Practical application and mechanism - Rong Cheng; Yating Chen; Peiwen Jiang; Jianzhong Zheng; Xiang Zheng (Chemical Engineering Journal, 2023)

Spatiotemporal changes of extreme climate indices and their influence and response factors in a typical cold river basin in Northeast China - Yating Ren; Feng Zhang; Chunli Zhao; Dongni Wang; Jiapeng Li; Jingjing Zhang; Zhiqiang Cheng (Theoretical and Applied Climatology, 2023)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Maochun Wei; Keyu Chen; Yating Lin; En Cheng (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out a lot of research on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure, in which the level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of P. vannamei are collected based on passive acoustic technology. Their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of P. vannamei to achieve the purpose of real-time monitoring of the behavior state of P. vannamei . The experimental results show that linear prediction cepstrum coefficient (LPCC) and Mel-frequency cepstrum coefficient (MFCC) characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of P. vannamei . Meanwhile, the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently and has classification accuracy as high as 93%.

Vegetation grows more luxuriantly in Arctic permafrost drained lake basins - Yating Chen; Aobo Liu; Xiao Cheng (Global Change Biology, 2021)
As Arctic warming, permafrost thawing, and thermokarst development intensify, increasing evidence suggests that the frequency and magnitude of thermokarst lake drainage events are increasing. Presently, we lack a quantitative understanding of vegetation dynamics in drained lake basins, which is necessary to assess the extent to which plant growth in thawing ecosystems will offset the carbon released from permafrost. In this study, continuous satellite observations were used to detect thermokarst lake drainage events in northern Alaska over the past 20 years, and an advanced temporal segmentation and change detection algorithm allowed us to determine the year of drainage for each lake. Quantitative analysis showed that the greenness (normalized difference vegetation index [NDVI]) of tundra vegetation growing on wet and nutrient‐rich lake sediments increased approximately 10 times faster than that of the peripheral vegetation. It takes approximately 5 years (4–6 years for the 25%–75% range) for the drainage lake area to reach the greenness level of the peripheral vegetation. Eventually, the NDVI values of the drained lake basins were 0.15 (or 25%) higher than those of the surrounding areas. In addition, we found less lush vegetation in the floodplain drained lake basins, possibly due to water logging. We further explored the key environmental drivers affecting vegetation dynamics in and around the drained lake basins. The results showed that our multivariate regression model well simulated the growth dynamics of the drainage lake ecosystem ( , p , p

Comprehensive characterization and gene expression patterns of LBD gene family in Gossypium - Jingwen Yu; Qianwen Xie; Cheng Li; Yating Dong; Shuijin Zhu; Jinhong Chen (Planta, 2020)
Main conclusion A comprehensive account of the LBD gene family of Gossypium was provided in this work. Expression analysis and functional characterization revealed that LBD genes might play different roles in G. hirsutum and G. barbadense . Abstract The Lateral Organ Boundaries Domain (LBD) proteins comprise a plant-specific transcription factor family, which plays crucial roles in physiological processes of plant growth, development, and stress tolerance. In the present work, a systematical analysis of LBD gene family from two allotetraploid cotton species, G. hirsutum and G. barbadense , together with their genomic donor species, G. arboreum and G. raimondii , was conducted. There were 131, 128, 62, and 68 LBDs identified in G. hirsutum , G. barbadense , G. arboreum and G. raimondii , respectively. The LBD proteins could be classified into two main classes, class I and class II, based on the structure of their lateral organ boundaries domain and traits of phylogenetic tree, and class I was further divided into five subgroups. The gene structure and motif composition analyses conducted in both G. hirsutum and G. barbadense revealed that LBD genes kept relatively conserved within the subfamilies. Synteny analysis suggested that segmental duplication acted as an important mechanism in expansion of the cotton LBD gene family. Cis-element analysis predicated the possible functions of LBD genes. Public RNA-seq data were investigated to analyze the expression patterns of cotton LBD genes in various tissues as well as gene expression under abiotic stress treatments. Furthermore, RT-qPCR results found that GhLBDs had various expression regulation under MeJA treatments. Expression analysis indicated the differential functions of cotton LBD genes in response to abiotic stress and hormones.

Speciated VOCs emission estimate for a typical petrochemical manufacturing plant in China using inverse-dispersion calculation method - Wei Wei; Yating Wang; Gan Yang; Li Yue; Shuiyuan Cheng (Environmental Monitoring and Assessment, 2018)

Associations between tumor necrosis factor alpha gene polymorphism and sarcoidosis: a meta-analysis - Hao Jun Xie; Muli Wu; Yi Niu; Bin Shen; Yating Huo; Yuanxiong Cheng (Molecular Biology Reports, 2014)

RNA interference-mediated repression of SmCPS (copalyldiphosphate synthase) expression in hairy roots of Salvia miltiorrhiza causes a decrease of tanshinones and sheds light on the functional role of SmCPS - Qiqing Cheng; Ping Su; Yating Hu; Yunfei He; Wei Gao; Luqi Huang (Biotechnology Letters, 2014)

Effects of hypoxia on osteogenic differentiation of rat bone marrow mesenchymal stem cells - Yating Wang; Juan Li; Yanmin Wang; Lei Lei; Chunmiao Jiang; Shu An; Yuxiang Zhan; Qian Cheng; Zhihe Zhao; Jun Wang; Lingyong Jiang (Molecular and Cellular Biochemistry, 2012)